Avaliação antropométrica, dietética e dos biomarcadores do metabolismo lipídico de pais de crianças e adolescentes com doenças reumáticas crônicas - Pereira, Lucila [UNIFESP] (2019)
Introduction: Chronic rheumatic diseases in children and adolescents increase short- and long-term cardiovascular risk. Thus, knowing the eating habits, biomarkers of lipid and glycidic metabolism and the lifestyle of patients and their parents will enable the development of strategies aimed at reducing this risk. Objectives: To describe the classification of body mass index, dietary intake, physical activity and lipid metabolism biomarkers of parents of children and adolescents with chronic rheumatic diseases and compare them with those of their children. Methods: Cross-sectional study with 91 parents and their respective children diagnosed with JIA (n = 30 / 33.0%), JSLE (n = 41 / 45.0%) and JDM (n = 20 / 22.0%). Anthropometry, dietary intake, physical activity, total cholesterol and fractions, triglycerides, and apolipoproteins A-I and B were evaluated. Data werw statistically treated using the SPSS statistical program, considering a significance level of 5% (p<0.05). To compare the categorical variables, the chi-square test or Fisher’s exact test was uded. Pearson’s correlation coefficient was tested for correlation between parent and child variables and the Cramer’s V test was used to verify association. Results: Most parents were female, as were their children (89.8 and 83.5% respectively). The average age of the parents was 40.5 ± 7.4 years. The disease follow up time was 4.5 ± 3.4 years and active disease was observed in 56% of children / adolescents. 80% of overweight children / adolescents also had parents with the same nutritional diagnosis. There was a moderate association to total lipid intake (Cramer's V test = 0.254; p = 0.037) and weak to saturated fat (Cramer's V test = 0.219; p = 0.050) and cholesterol (Cramer's V test = 0.234; p = 0.025) between parents and their children. When the daily protein intake in grams of kilo weight was evaluated, there was a positive linear correlation (corr=0.2239; p=0.033) between parents and children. The prevalence of dyslipidemia (TC, LDL-c, HDL-c, non-HDL-c and TG) of the parents’ children / adolescents was 83.5% and 82.4% respectively. Both parents and children / adolescents mostly had low HDL-c (52.8 and 64.8% respectively). Conclusion: The present study draws attention to the high prevalence of overweight, dyslipidemia, physical inactivity and central adiposity in the parents of children and adolescents with chronic rheumatic diseases. There was an association between inadequate fat consumption by parents and their children; this did not occur for BMI classification, lipid profile and for physical activity. The findings point to the importance of intervention strategies with parental involvement.